Epidemiology of COVID-19 in patients of a Social Security Institution in Tabasco, México - Azuara-Forcelledo, Humberto; Jiménez-Sastré , Alejandro; Marenco-Juárez , José Manuel; Guzmán-Priego, Crystell Guadalupe; Concepción López, Alejandro (Horizonte Sanitario, 2021)
Objective: to determine the epidemiological characteristics of COVID-19 cases presented in the ISSET in the period from March 1, 2020 to January 18, 2021.Material and method: descriptive, cross-sectional and retrospective study at the Social Security Institute of the State of Tabasco (ISSET), Mexico, in the period from March 01, 2020 to January 18, 2021.Results: 4,283 positive cases were registered for SARS-CoV-2, by rt-PCR, with the highest incidence of cases in women with 51.04% of cases aged 50 to 54 years, and 21% corresponding to health personnel entitled. The mortality rate was higher in men aged 60 to 64 years, associated with comorbidities, such as hypertension, diabetes, and obesity.Conclusion: the incidence of SARS-CoV-2 cases has been increasing. In the period from March 1, 2020 to January 18, 2021, 4,283 positive cases of SARS-CoV-2 were reported, affecting health personnel. A higher mortality rate was observed in adults over 60 years of age, which increases when associated with various comorbidities.Keywords: SARS-CoV-2; COVID-19; comorbidity; incidence; mortality.